Otherwise, inoperable. The role of ECMO in thoracic surgery – focus on the mediastinum - Pinto, Carlos (2025)
The use of extracorporeal membrane oxygenation (ECMO) in surgery is expanding as the medical community started adopting it, with good results, for procedures with high risk of respiratory and hemodynamic instability. This technique provided the possibility to reduce the number of patients previously considered inoperable because of these limitations.   Thymic epithelial tumors (TETs) are rare neoplastic mediastinal lesions, with a reported incidence of 0.3 per million. They are indolent and associated with a delayed diagnosis, as symptoms arise late. Some can reach such dimensions that surgery without ECMO support would render these patients at risk of heart/great vessels or/and respiratory compression of prohibitive surgical risk or even inoperable. This report aims to update information on ECMO support in surgery for prevascular mediastinal masses, focusing on pre-operatory assessment, ECMO implantation, patient selection and surgical results.